1998
DOI: 10.1046/j.1365-2249.1998.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of IL-6 biological activities by activin A and implications for inflammatory arthropathies

Abstract: Activin A is a cytokine whose multiple functions have yet to be fully determined. In this study, the role of proinflammatory cytokines in regulatory control of activin A production was shown in synoviocytes and chondrocytes. Additional facets of functional inflammation-related activities of activin A were also determined. Results showed that activin A concentrations in the synovial fluid of patients with rheumatoid arthritis and gout were elevated relative to those in patients with osteoarthritis. Further stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 28 publications
3
57
0
2
Order By: Relevance
“…It was found that the ability of the stroma to suppress the growth of plasmacytomas is due to secretion of activin A, a cytokine member of the transforming growth factor (TGF) ␤ superfamily. [20][21][22][23] This phenomenon is highly specific since other normal and tumor hemopoietic cells from different lineages were resistant to activin A. Our studies further showed that activin A kills plasmacytomas by antagonism with the survival signal of IL-6.…”
Section: Introductionsupporting
confidence: 56%
“…It was found that the ability of the stroma to suppress the growth of plasmacytomas is due to secretion of activin A, a cytokine member of the transforming growth factor (TGF) ␤ superfamily. [20][21][22][23] This phenomenon is highly specific since other normal and tumor hemopoietic cells from different lineages were resistant to activin A. Our studies further showed that activin A kills plasmacytomas by antagonism with the survival signal of IL-6.…”
Section: Introductionsupporting
confidence: 56%
“…Activin is produced at sites of inflammation (31)(32)(33) and has been shown to play a role in wound healing in mice (34). It may also be involved in bone formation since inhibin ␤A-chain knockout mice have craniofacial abnormalities (35).…”
Section: Discussionmentioning
confidence: 99%
“…Activins/inhibins are evolutionarily conserved, broadly distributed, 48 and influence many other processes, including inflammation, acute phase reaction, 49 proliferation and cell growth, 50 nerve cell survival and differentiation, 51,52 tissue repair and wound healing, 53,54 angiogenesis 55 and matrix and bone remodeling via BMPs (eg inhibition of osteoclastic cathepsin K-mediated bone reabsorption). [56][57][58][59][60][61] A role of activin in the pathogenesis of inflammatory arthropathies has been suggested by Yu et al 62 The latter demonstrated significantly elevated levels of activin A in the synovial fluid of patients with rheumatoid arthritis and gout, relative to those with osteoarthritis. The production of activin A by synoviocytes and chondrocytes in culture is up-regulated by cytokines such as IL-1, TGF-␤, interferon-␥, and IL-8.…”
Section: Figure 5 Real-time Pcr For Activin and Follistatin Real-timmentioning
confidence: 99%